A Comparison of Assay Performance Measures in Screening Assays: Signal Window, Z′ Factor, and Assay Variability Ratio - Iversen, Philip W.; Eastwood, Brian J.; Sittampalam, G. Sitta; Cox, Karen L. (Journal of biomolecular screening, 2006)
In this article, the authors compare the assay performance measures, signal window, Z' factor, and assay variability ratio. They examine their mathematical formulae for similarities and differences, describe their statistical sampling properties using the results of a computer simulation, and illustrate their use with example data. Based on these results, the authors recommend the Z' factor as a preferred measure of assay performance for screening assays and point out that none of these measures are adequate for characterizing concentration-response assays.